(untitled) (Journal of Dhaka Medical College, 2021)
Background: Hair loss is a worldwide problem with significant prevalence in the developed countries. Although many pathophysiological factors have been involved in the development of hair loss, its etiology is still unclear. Trace elements. Objective: To assess duration of hair loss with serum iron level in alopecia. Methods: This cross sectional study was carried out in the Department of Physiology, Dhaka Medical College, Dhaka during January 2017 to December 2017. Serum iron level was estimated by flame atomic absorption spectrophotometry of thirty five newly diagnosed hair loss patients aged 18 to 45 years were study group and thirty five ages, sex and BMI matched healthy subjects were control group. Both male and female was assessed by analyzing time. In this study, the duration of hair loss was 1 to 18 months. Duration of hair loss in study group was divided in two groups such as ≤2 months and >2 months. Patients were selected from Department of Dermatology and Venerology, Dhaka Medical College Hospital, Dhaka. For statistical analysis Unpaired Student’s‘t’ test, Chi square tests and Pearson’s correlation coefficient (r) tests were performed. Results: In this study, serum iron level showed negative correlation with the duration of disease in study group. Conclusions: From this study, it is concluded that serum iron deficiency is associated with duration of hair loss patients. J Dhaka Medical College, Vol. 29, No.1, April, 2020, Page 29-32